PELATIHAN AKUNTANSI SEDERHANA UNTUK KEPALA DESA DI KECAMATAN PANGKALAN BUNUT KABUPATEN PELALAWAN - wardi, jeni; liviawati, liviawati; putri, gusmarila eka (Komunitas Manajemen Kompetitif, 2018)
Since the existence of regional autonomy, the structure of government is divided into Central Government and Local Government. Regional Government consists of Provincial Government and Regency / City Government. After the enactment of Law of the Republic of Indonesia Number 6 Year 2014 on Village, Village then has the authority also as an autonomous region. Villages are given a great opportunity to manage their own governance, including the implementation of development to improve the welfare and quality of life of village communities. Bunut sub-district is one of the sub-district of Pelalawan regency, which is expanded from Kampar Regency, based on the Law of the Republic of Indonesia, number: 53 year 1999. Currently Bunut Sub-district has been expanded into: Kecamatan Bandar Petalangan. Bunut District itself as the District Induk, and District Bandar Petalangan as subdistrict of pemekaran. As it is new, the human resources capabilities related to accountability reporting and financial management transparency have not gone well and face many obstacles. Therefore the purpose of this dedication is to provide simple accounting training, and socialization of internal control system related to sound financial management. The result of the dedication to the village head in Pangkalan Bunut Sub-district is the participants are very enthusiastic to follow the activity, there is a very interesting discussion related to the problems that are being faced by the participants in the financial practice and the input given by the team of dedication